Medical Informatics Education at the University of Manchester - Kay, S.; Hillier, V.F.; Rector, A.L.; Taylor, C.J. (Yearbook of Medical Informatics, 1997)
Manchester University offered the first full time, undergraduate Medical Informatics degree programme in the UK. The B.Sc. in Medical Informatics was conceived in 1992 and its first cohort of students, taking the three year version, graduated in 1996; those students taking the four year version of the undergraduate degree will graduate in July 1997. The paper describes our somewhat turbulent experience of the first four years, highlighting both the difficulties and successes of launching an inter-disciplinary degree. First, the story of the programme’s development is given by way of an introduction and to establish a suitable context for describing the programme in more detail. Then, after presenting the aim and objectives of the programme, we describe the overall structure of the course, and reflect upon certain key issues for establishing Medical Informatics as a distinct, academic discipline.
Keywords: Medical Informatics; Undergraduate, B.Sc.; Awareness